Quality in education: a theoretical discussion on the Brazilian educational system (Research, Society and Development, 2020)
This article portrays a view of the Brazilian scenario in the educational context. It is noticed that quality is a very discussed point in Brazilian education, it can be seen that this concept / category / paradigm is often used in multiple ways. Therefore, this text aims to: present the debate on the definition of quality education; discuss about: the Common Base National Curriculum-BNCC and the Knowledge of Natural Sciences in Elementary Education; demonstrate one of the evaluative policies carried out in Brazil in basic education. To this end, a bibliographic study of texts with a theme focused on teaching in the country, educational policies and even on the BNCC was carried out, with the aim of analyzing the Brazilian educational system. Finally, it was found that despite the fact that public policies are advancing in terms of projects to improve education, there is still a long way to reach educational quality.